Convergence Sublayer Analysis and Implementation on Medium Access Control Layer using The Embedded Configurable Operating System - Febri Dawani; Tri Brotoharsono; Setyorini (School of Computing, Telkom University, 2023)
This study explores the implementation of the Convergence Sublayer (CS) defined in IEEE Std 802.16TM-2004. The CS, situated atop the Medium Access Control Layer, plays a crucial role in classifying and mapping MAC Service Data Units (MSDU) to specific connections identified by Connection Identifiers (CID). Using the Embedded Configurable Operating System (eCos), an Open Source Real-Time Operating System, this research successfully demonstrates the implementation of MAC CS on a specific hardware platform. The findings indicate that eCos facilitates the efficient execution of MAC CS's classification and mapping functions.